Human Trafficking in Cambodia: Reintegration of the Cambodian illegal migrants from Vietnam and Thailand - Neth, Naro (2016)
Human trafficking is a deep concern at global, regional and state level. It is multi-pronged and linked to the problem of human rights, human dignity and HIV/AIDS as some female victims were forced into commercial sex and prostitution. In the 21st century, human trafficking is considered a criminal crime that all states need to address. The problem of human trafficking in Cambodia arose from poverty as the root cause wherein the poor wish to find income opportunities and hence became victims of trafficking into Thailand and Vietnam. In the process of helping those victims to return to their home countries, reintegration is considered crucial to help them meet better living conditions. Many factors have contributed to successful reintegration. Among those factors are job training and employment as the most important prerequisites of a reintegration programme. However, after the reintegration programme the victims are still facing income difficulties due to the inability of those rendering aid to look more in-depth with regard to the concept of job training and employment. Hence, this paper attempts to answer the question “What can the government, NGOs and private sector do more to help the victims? What are the particular needs of the victims? And is reintegration a success?” The paper seeks to examine whether reintegration is really helpful in assisting victims to obtain a better job and contribute towards helping their families. If reintegration is not really helpful, and the root cause of trafficking still remains, then the reintegration process will not succeed. Successful reintegration should resolve an entire range of problems faced by the victims and their families; in particular, poverty as the root cause of human trafficking has to be addressed.